Patterns of Rectal Temperature and Shipping Fever Incidence in Horses Transported Over Long-Distances - Maeda, Yousuke; Oikawa, Masa-aki (Frontiers in Veterinary Science, 2019)
Shipping Fever is a transport associated syndrome seen in equids and bovines transported over long distances. The microbial profile and clinical signs vary between species, and in horses it is characterized by pharyngeal commensal bacteria and aerosolized particulate matter invading the lower airway due to compromised mucocillary clearance mechanisms during transports. This leads to pyrexia, pulmonary parenchymal disease, inappetence, and in severe cases pleuropneumonia. It has been shown that the incidence of transport-related pyrexia in horses increases with travel time and distance, however, this incidence rate has been expressed as the cumulative number of horses showing pyrexia with the length of travel time during road transport (cumulative percentage), which does not accurately reflect the actual temperature fluctuations and their patterns in relation to shipping fever. This study aims to demonstrate the individual fluctuations of body temperature variations during transport, particularly febrile changes. 53 Anglo-Arab and Thoroughbred horses aged 23 to 30 months were transported by road over different distances and durations (36˗61 hours; 1,492˗2,921 km) in 3 investigations carried out in the spring and mid-summer in the northern hemisphere. The results showed that the incidence of fever (characterized by rectal temperature ˃38.6oC) was highest from 20 to 49 hours after the start of transport. Clinical signs of shipping fever was observed in 25 of the 53 horses (47.2%), of which 10 horses (18.9%) exhibited fever at the end of transportation and 15 horses (28.3%) did not. This showed that horses that develop shipping fever do not necessarily present with fever at the end of transportation. Necropsy of 20 horses performed immediately after transportation suggested that transport induced pneumonia, contributed to the onset of pyrexia. This finding supports the suggestion that measuring body temperature upon arrival to determine the presence or absence of shipping fever could result in missed diagnoses for some horses with subclinical pneumonia, and that taking multiple temperature measurements at intervals from 20 hours of transportation is a simple method for not missing horses with subclinical pneumonia.